2021
DOI: 10.1155/2021/7534607
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical and Radiographic Evaluation of Zirconia Dental Implants: 10-Year Follow-Up

Abstract: Purpose. The aim is to evaluate the survival and success rates, as well as the marginal bone loss (MBL) and periodontal indexes, of zirconia implants with 10-year follow-up. Materials and Methods. 10 patients were selected and 26 one-piece zirconia implants were used for the rehabilitation of single tooth or partially edentulous ridge. After 10 years, a clinical-radiographic evaluation was performed in order to estimate peri-implant tissue health and marginal bone loss. Results. The survival and success rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Therefore, this approach was chosen in this study. Moreover, the per-mucosal part of the one-piece implant was custom-made to fit the anatomical site, and to improve tissues healing [ 13 ]. Bacterial accumulation and leakage from the implant-abutment connection, and its harmful effects on MBR were neutralized by the one-piece design of this zirconia implant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this approach was chosen in this study. Moreover, the per-mucosal part of the one-piece implant was custom-made to fit the anatomical site, and to improve tissues healing [ 13 ]. Bacterial accumulation and leakage from the implant-abutment connection, and its harmful effects on MBR were neutralized by the one-piece design of this zirconia implant.…”
Section: Discussionmentioning
confidence: 99%
“…Also, allergic reactions to titanium have been reported [ 11 ]. Zirconia appears to be a suitable implant material due to its tooth-like color, mechanical properties, biocompatibility and low plaque affinity [ 12 , 13 ]. Zirconia dental implants could be alternative to titanium implants that may show dark unfavorable shade through peri-implant soft tissues.…”
Section: Introductionmentioning
confidence: 99%
“…TA B L E 1 Characteristics of clinical studies investigating implant survival. One study did not provide any information regarding MBL (Brunello et al, 2022), 5 studies used periapical radiographs to determine MBL between implant placement and the last follow-up investigation (Balmer et al, 2020;Borgonovo et al, 2021;Gahlert et al, 2022;Grassi et al, 2015;Kohal et al, 2020).…”
Section: Peri-implant Mblmentioning
confidence: 99%
“…Based on the eligibility criteria, only observational studies were included for data extraction and further statistical analysis. 48 implants) were included in the analysis ( [Balmer et al, 2020;Borgonovo et al, 2021;Brunello et al, 2022;Gahlert et al, 2022;Grassi et al, 2015;Kohal et al, 2020], [ Table 1]). The risk of bias assessment of these studies is shown in Table 6.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Furthermore, it displays unique mechanical properties such as high fracture resistance, high bending strength, high corrosion resistance, and radiopacity. Lower bacterial adhesion reduces the likelihood of inflammation in peri-implant tissues, and also encourages the usage of zirconia ceramic ( Bona et al, 2015 ; Borgonovo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%